Unblending Borderline Personality and Bipolar Disorders. (August 2017) - ,; di Giacomo, Ester; Clerici, Massimo; Aspesi, Flora; Aguglia, Eugenio; Barone, Lavinia; Bellino, Silvio; Bozzatello, Paola; Brignolo, Elena; Carpiniello, Bernardo; Colmegna, Fabrizia; Ghiani, Alice; et al.
Abstract: Borderline Personality (BPD) and Bipolar (BP) disorders stimulate an academic debate between their distinction and the inclusion of Borderline in the Bipolar spectrum. Opponents to this inclusion attribute the important differences and possible diagnostic incomprehension to overlapping symptoms. We tested 248 Borderline and 113 Bipolar patients, consecutively admitted to the Psychiatric Unit, through DSM-IV Axis I and II Disorders (SCID-I/II), Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A), Young Mania Rating Scale (YMRS) and Borderline Personality Disorder Severity Index-IV (BPDSI-IV). All the tests statistically discriminated the disorders (p < 0.0001). Overlapping symptoms resulted significantly different (impulsivity = 5.32 in BPD vs 1.55 in BP, p < 0.0001; emotional instability = 7.11 in BPD vs 0.55 in BP, p < 0.0001) and the range of their scores gives the opportunity for an even more precise discrimination. Distinctive traits (e.g. irritability or sexual arousal) are also discussed in order to try to qualify the core of these disorders to a higher degree. Comorbidity proves to be extremely small (3.6%). However, Borderline patients with manic features offer a privileged point of view for a deeper analysis. This allows for the possibility of a more precise examination of the nature and load of each symptom. Borderline Personality and Bipolar Disorders can be distinguished with high precision using common and time-sparing tests. The importance of discriminating these clinical features may benefit from this evidence.